Differences Of Education Systems In Developed And Developing Countries Curriculum, Educators And Financing In Indonesia And Finland - Setiawan, Wahyu Agus (Didaktika Religia, 2018)
The education system is a whole component of education that is interrelated with one another. Better education system of a country will have a straightforward impact on the quality of the people in the country. The education system in Indonesia and Finland has differences and similarities. Teachers are both given autonomy to develop their teaching. Finland school is a place to grow and develop and is not a place to play and get scores but in Indonesia it is still score oriented, parents will be proud of their children who get good grades. In terms of educator recruitment, Finland set a minimum standard of S2 while in Indonesia at least S1. On the aspect of financing in Indonesian education, it still gets fund from students, but the government provides a variety of educational assistance at all levels such as BOS funds so that at the elementary and junior high school levels the cost of education is free because it is already covered by government assistance funds. Whereas Finland eliminates all education costs at all levels.